Norské parlamentní volby 2005 - Kolbaba, Radovan, 1983-; Kopeček, Lubomír, 1975-; Masarykova univerzita. Katedra politologie (2006)
Práce se zabývá norskými parlamentními volbami konanými v září roku 2005 v Norském království. Na úvod seznamuje čtenáře s politickým, volebním i stranickým systémem Norska. Snaží se popsat faktory jež ovlivňovaly rozhodování norských voličů - programy stran, vystupování jejich zástupců v médiích, či předvolební průzkumy. Dále se věnuje samotnému průběhu voleb. Popisuje nejen výsledek celostátní, ale i rozvrstvení hlasů v norských krajích. Na závěr představuje novou norskou vládu a rozebírá, co nového tyto volby přinesly.
This work deals with the norwegian parliamentary elections held in September 2005 in the Kingdom of Norway. The opening chapter acquaints the reader with the political, electoral and party system of Norway. It tries to describe the factors, that influenced decision of the norwegian voters parties programs, performance of their representatives in the media or preelectionary research for public opinion. This work also concerns the course of the elections itself. It describes not only the national results, but also the layout of the votes in the norwegian counties. Finally, it introduces the new norwegian government and analyzes, what new these elections have brought.
Vedoucí práce: Lubomír Kopeček.
Bakalářská práce (Bc.)--Masarykova univerzita, Fakulta sociálních studií, 2006.
Keywords: parlamentní volby; parliamentary elections; Norsko; Norway; bakalářské práce